2009
DOI: 10.1128/jvi.01439-09
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Strains of Influenza A Viruses Do Not Induce Degradation of RNA Polymerase II

Abstract: We have previously shown that infection with laboratory-passaged strains of influenza virus causes both specific degradation of the largest subunit of the RNA polymerase II complex (RNAP II) and inhibition of host cell transcription. When infection with natural human and avian isolates belonging to different antigenic subtypes was examined, we observed that all of these viruses efficiently induce the proteolytic process. To evaluate whether this process is a general feature of nonattenuated viruses, we studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 76 publications
0
39
0
Order By: Relevance
“…Previous studies found that influenza virus infection causes the specific degradation of the hypophosphorylated form of the largest subunit of Pol II. The degradation was dependent on viral polymerase and the proteolytic activity of PA (26,27). A recent study reported that the hyperphosphorylated form of Pol II was also degraded during influenza virus infection and that the proteasome pathway was involved in the degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found that influenza virus infection causes the specific degradation of the hypophosphorylated form of the largest subunit of Pol II. The degradation was dependent on viral polymerase and the proteolytic activity of PA (26,27). A recent study reported that the hyperphosphorylated form of Pol II was also degraded during influenza virus infection and that the proteasome pathway was involved in the degradation.…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that Pol II degradation may represent a viral strategy to subvert the host antiviral system (31). Other studies pointed out that attenuated influenza virus strains did not cause Pol II degradation, suggesting that the Pol II degradation may be linked with virulence (26). We also found that the level of the hypophosphorylated form of Pol II was decreased in A/WSN/33-infected cells compared to that in uninfected cells (data not shown), but the Finally, CDK9 activity may be modified during influenza virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Two other viruses, herpes simplex virus and influenza A virus, were previously shown to trigger degradation of RNAP II (61)(62)(63)(64). However, for both these viruses, levels of total RNAP II or of IIa are affected rather than preferentially IIo as in the case of LACV.…”
Section: Discussionmentioning
confidence: 99%
“…However, for both these viruses, levels of total RNAP II or of IIa are affected rather than preferentially IIo as in the case of LACV. Herpes simplex virus achieves RNAP II degradation through the proteasomal system (61,62), whereas for influenza A virus the proteolytic viral protein PA is responsible (63,64). It should be noted that, in contrast to LACV, these viruses are directly dependent on RNAP II activity.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a degradative process affecting RNA polymerase II (RNAP II) (9)(10)(11), as well as CHD6 chromatin remodeler (12), has been reported. Degradation and disabling of host cell factors involved in genome expression may contribute to hijacking the metabolism of the infected cell and to suppressing the establishment of the host antiviral defense against viral pathogens, contributing to viral pathogenicity.…”
mentioning
confidence: 99%